Mixed-phase regime cloud thinning could help restore sea ice - Villanueva, Diego; Possner, Anna; Neubauer, David; id_orcid:0 000-0002-9869-3946; Gasparini, Blaž; Lohmann, Ulrike; id_orcid:0 000-0001-8885-3785; Tesche, Matthias (IOP Publishing, 2022)
Cloud geoengineering approaches aim to mitigate global warming by seeding aerosols into clouds to change their radiative properties and ocurrence frequency. Ice-nucleating particles (INPs) can enhance droplet freezing in clouds, reducing their water content. Until now, the potential of these particles has been mainly studied for weather modification and cirrus cloud thinning. Here, using a cloud-resolving model and a climate model we show that INPs could decrease the heat-trapping effect of mixed-phase regime clouds over the polar oceans during winter, slowing down sea-ice melting and partially offsetting the ice-albedo feedback. We refer to this concept as mixed-phase regime cloud thinning (MCT). We estimate that MCT could offset about 25% of the expected increase in polar sea-surface temperature due to the doubling of CO2. This is accompanied by an annual increase in sea-ice surface area of 8% around the Arctic, and 14% around Antarctica. ISSN:1748-9326 ISSN:1748-9318